Forum-Shifting and Human Rights: Prospects for Queering the Women, Peace and Security Agenda - Hagen, Jamie; O'Rourke, Catherine F. (Human Rights Quarterly, 2023)
The adoption of the Women, Peace and Security (WPS) Agenda by the UN Security Council constituted a forum-shift by women’s rights advocates away from the human rights system. As queer critique of the WPS agenda gathers pace, this article reflects on the antecedents of the queer exclusions of the WPS agenda in international human rights law. The article thereby reveals the consequences in other international law regimes of human rights law’s queer exclusions. The article concludes with some tentative proposals to utilise the pluralism of international human rights law to expand queer possibilities for both human rights and WPS.
EPrint Processing Status: Full text deposited in DRO